Drivers affecting the relation between biodistricts and school meals initiatives: evidence from the Cilento biodistrict - Kraljevic, Beatrice; Zanasi, Cesare (Frontiers in Sustainable Food Systems, 2023)
Biodistricts (also known as “organic districts” or “eco-regions”) are receiving increasing attention by scholars and public institutions. This interest is based largely on the biodistricts’ focus on linking organic agriculture with the socio-economic, cultural and ethical aspects of the areas in which they are located. Furthermore, these realities are in line with recent EU initiatives aimed at promoting sustainable practices, such as Green Public Procurement and others included in the Farm to Fork strategy. The rising awareness of sustainability, food safety and security within schools has made Public School Food Procurement (PSFP) one of the potential drivers supporting the biodistricts’ development. Despite its relevance, research on this topic is relatively scarce. The present study seeks to assess the drivers influencing the integration between biodistricts and organic PSFP. A theoretical and an analytical framework tool were developed to this end and applied to the Cilento Biodistrict, where organic PSFP is currently active. The research highlighted different drivers positively affecting the access of the Cilento Biodistrict to organic PSFP, mainly related to its collaborative nature and the interest in adopting more sustainable practices. However, characteristics of local organic production such as high prices and insufficient volumes negatively impact the relationship with organic public school canteens. Considering the relatively homogeneous characteristics of these realities, the study provides a reference framework for further research and policies supporting the relationship between organic school meals initiatives and biodistricts.